Eco-balance y medidas de gestión ambiental en la obtención de etanol en la fábrica artesanal de aguardiente “No te piques” - Romero Ortega, Ángel Andrés (2024)
The general objective of the research was focused on proposing environmental management measures after the elaboration of a detailed eco-balance of the raw material that enters and leaves the 3 production processes to obtain artisanal alcohol (grinding, fermentation and distillation). The methodology used two methods, quantitative and qualitative, observation, survey and documentary analysis techniques. This study was carried out at the "No te piques" Artisanal Brandy Factory, located at the Agua Fria site in the Junín canton, Manabí, Ecuador, located at 0°54'36.4" south latitude and 80°10'49.5" west longitude. The elaboration of the eco-balance revealed that 950 kg of raw material entered and an output of 979.40 kg was obtained, which should be equal to the amount that entered. However, a mass increase of 4% was identified in the sum of all outputs, indicating an error in the process. This finding underscores the need to consider all the factors involved in ethanol processing. As a result of this 4% error, environmental management measures applicable to the company are proposed, including improvements in the three processes to increase their performance, economically value the two wastes generated (bagasse and vinasse) and provide training on environmental issues to the owner and staff.